Impact of sex in stroke thrombolysis: a coarsened exact matching study - Hametner, Christian; Kellert, Lars; Ringleb, Peter A. (BMC neurology, 2015)
It is not established whether sex influences outcome and safety following intravenous thrombolysis (IVT) in acute stroke. As a significant imbalance exists between the baseline conditions of women and men, regression analysis alone may be subject to bias. Here we aimed to overcome this methodical shortcoming by balancing both groups using coarsened exact matching (CEM) before evaluating outcome.
Gesehen am 25.03.2021